(untitled) (Revista de Ciências Agroveterinárias, 2020)
Araçá (Psidium cattleianum Sabine) is a native fructiferous species, of great economic importance in pharmaceutical and food industry. Therefore, there is a need to produce good quality seedlings capable of meeting market demands. The objective of this work was to evaluate the influence of the environment and the use of slow release fertilizer Osmocote® on the development of araçá seedlings. Araçá seeds were collected in March 2015 and germinated. After approximately 90 days, the seedlings were arranged for the treatments. The treatments consisted of five doses of fertilizer (0; 3.0; 6.0; 9.0 e 12.0 g L-1) and two environments, greenhouse and shade house (50%) in factorial scheme 5 x 2. At 210 days, we evaluated the height of seedlings (cm); collar diameter diameter (mm); dry weight of shoot and root (g) and chlorophyll index (SPAD). There was interaction of the factors for most of the variables, with the exception of the chlorophyll index. The intermediate dose of the fertilizer implicated in the best performance of growth of seedlings in almost all the occasions, as well as the shaded environment. For araçá seedlings, the use of 6 mg L-1 of fertilizer and a shade house environment are recommended for its better development.